Peningkatan Berpikir Kritis dan Kreatif pada Pelajaran Matematika ditinjau dari Jenjang Satuan Pendidikan - Moch. Syakroni; Endang Suprapti; Junaidi Fery Efendi (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2021)
Critical and creative thinking has a vital role in answering lessons, especially in mathematics learning. The purpose of this study was to determine the improvement of critical and creative thinking in mathematics lessons from each level of education unit based on cycle I and cycle II and to describe the application of the mathematics learning model. This study uses a systematic literature review research method by identifying, reviewing, evaluating, and interpreting the research that has been done. Based on data obtained from the Google Scholar website, URL (sholar.google.com) with the help of the Publish or Perish application in 2016-2021. The results showed 1) there was an increase in critical and creative thinking in mathematics learning in terms of educational units based on cycle I and cycle II so that the average results obtained from each level were in the range of values ​​of 50% to 83% on achieving the indicators of class action success. 2) Success in improving students' critical and creative thinking skills is found in how teachers master the application of learning models when providing material in class. Researchers suggest that in improving critical and creative thinking in mathematics lessons at every level of the education unit, teachers can use the Discovery Learning learning model for elementary/equivalent levels. Meanwhile for SMP/Equivalent can use Realistic Mathematics Education and at the SMK/Equivalent level can use the Open-Ended Approach.